The Legal Basis for Nuclear Weapons Ban - Abdul Hakim Thamer, Researcher. Ayat; Jabbar Craidy, Prof. Dr. Ali (Basra studies journal, 2024)
One of the most dangerous wars humanity faces is those involving nuclear weapons, as this type of weaponry does not distinguish between military personnel and civilians; it often affects civilians more than military personnel. The danger of using nuclear weapons became apparent after their first use at the end of World War II against Japan. Hiroshima and Nagasaki, two Japanese cities, were bombed on the sixth and ninth of August 1945, respectively, with two limited-size nuclear fission bombs whose destructive power equaled millions of tons of conventional bombs and projectiles, leading to the destruction of both cities. Consequently, the international community moved to establish rules prohibiting this type of weaponry. Many international agreements were concluded to prevent the manufacture and use of nuclear weapons. The United Nations also made significant efforts to prevent the proliferation of nuclear weapons. The General Assembly issued numerous resolutions to make the Middle East a nuclear-weapon-free zone, with the United Nations playing a significant role in this endeavor. The prohibition and banning of nuclear weapons find their basis in the United Nations Charter, which prohibits the threat or use of force in international relations. Moreover, these weapons violate the right to life enshrined in Article 6 of the International Covenant on Civil and Political Rights. Additionally, the use of nuclear weapons contradicts the principles and provisions of international humanitarian law, which aim to protect and respect individuals in armed conflicts, provide the necessary means to preserve and respect their lives, and alleviate the suffering resulting from hostile acts to the extent permitted by military necessity.